Effects of Physical Activity or Exercise on Depressive Symptoms and Self-Esteem in Older Adults: A Systematic Review - María Muñoz Pinto; Felipe Montalva-Valenzuela; Claudio Farías-Valenzuela; Paloma Ferrero Hernández; Gerson Ferrari; Antonio Castillo-Paredes (Psychiatry International)
There is a high prevalence of depression in older adults, and it is on the rise. However, exercise or physical activity can help improve mental health conditions, specifically depression and self-esteem. Therefore, the objective of this systematic review (INPLASY202360094) is to describe and analyze the effects of physical activity or exercise interventions on depressive symptoms and self-esteem in older adults. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a search strategy was carried out in four databases (PubMed, SciELO, WoS, and Scopus). Inclusion criteria: Studies that used physical activity or exercise as an intervention to improve depressive symptoms and self-esteem in older adults. The Physiotherapy Evidence Database scale and the Risk of Bias 2 tool were used to evaluate the quality of the articles. To synthesize the information from the studies, it was ordered based on author names, intervention, frequency, analysis, and results. Seven investigations met the selection criteria. It is concluded that physical activity or exercise improves self-esteem, depression, anxiety, physical fitness, and functionality in older adults. Therefore, it is a viable option for additional or complementary treatment aimed at achieving a comprehensive improvement in the lives of this population.